ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR), PROFITABILITAS, KINERJA PERUSAHAAN, DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2016-2018) - Ardianti Harun; Noor Shodiq Askandar; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
Financial statement integrity is the ability to present financial reports that show the actual condition of the company without being hidden. Its high-integrity financial statements can be utilized as a decision-making tool and can increase the trust of interested parties. This study aims to analyze the effect of corporate social responsibility (CSR), profitability, company performance, and audit quality on the integrity of financial statements. The research data used came from manufacturing companies listed on the Stock Exchange in 2016-2018, sampling was carried out using a purposive sampling method obtained by 26 manufacturing companies listed on the Stock Exchange. The data analysis method used is multiple linear regression analysis. The results of this study indicate that simultaneously the independent variables, corporate social responsibility (CSR), profitability, company performance, and audit quality affect the integrity of financial statements, while partially only profitability variable does not affect the integrity of financial statements.  Keywords: Corporate Social Responsibility (CSR), Profitability, Company Performance, Audit Quality and Integrity of Financial Statements.